2015
DOI: 10.1128/jcm.03067-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Characteristics of Klebsiella pneumoniae Associated with Bacteremia among Patients with Pneumonia

Abstract: e Some important virulence factors have been elucidated in Klebsiella pneumoniae infections. We investigated the relationship between virulence factors and multilocus sequence types (STs) and assessed the risk factors for bacteremia in patients with pneumonia due to K. pneumoniae. From April 2004 through April 2012, a total of 120 K. pneumoniae isolates from patients with pneumonia (23 with bacteremia and 97 without bacteremia) were collected from 10 medical institutions in Japan. Additionally, 10 strains of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 41 publications
4
39
0
1
Order By: Relevance
“…The isolate belongs to ST1612, which has been found in Japan (1). Because Japanese ST1612 isolates do not produce KPC-2, the South Korean isolate probably acquired the plasmid bearing bla KPC-2 from other species or a clone.…”
mentioning
confidence: 99%
“…The isolate belongs to ST1612, which has been found in Japan (1). Because Japanese ST1612 isolates do not produce KPC-2, the South Korean isolate probably acquired the plasmid bearing bla KPC-2 from other species or a clone.…”
mentioning
confidence: 99%
“…This study identified ST23 as the most common genotype, which were reported in many previous hospital-acquired infection studies in Asia [12, 13]. Noticeable this study isolated one ST65 strain, a mucoid phenotype and harbored rmpA gene for aerobactin, which more likely caused community-acquired infection [14, 15] and indicated as one of the independent risk factors for bacteremia in patients with pneumonia [13]. Moreover, the microbiological character of newly detected ST2362, ST2363, ST2364, ST2365, ST2366, ST2367, ST2368, ST2369, and ST2370, these strains presented clinical character are not thoroughly explicit, which needs further studies.…”
Section: Discussionmentioning
confidence: 56%
“…A recent study found over 150 distinct phylogenetic lineages of this pathogen and suggested that more remain to be identified (25). Many of these lineages can be found within a single hospital (26,27) and even within an individual patient (28), yet genotyping studies indicate that a relatively small number of lineages are responsible for a disproportionately large number of pneumonia cases (25,(29)(30)(31). For example, multilocus sequence typing has indicated that sequence type 11 (ST11), ST14, ST15, ST42, ST43, ST258, ST340, ST416, and ST512 strains are frequent causes of pneumonia over large geographic regions (25).…”
mentioning
confidence: 99%